Who seeks treatment for gaming? Characteristics of young and adult patients seeking treatment for gaming disorder - Bore, Per; Andersson, Mitchell; Nilsson, Sara; Oehm, Kajsa; Cervin, Matti; Håkansson, Anders; Claesdotter-Knutsson, Emma (Frontiers in Psychiatry, 2025)
BackgroundGaming disorder has recently been recognized as a psychiatric condition, yet the clinical characteristics of treatment-seeking individuals remain understudied. This study examined youth and adults seeking treatment at a specialized outpatient clinic in southern Sweden.MethodsA total of 107 individuals aged 12–49 years (M = 22.1, SD = 7.2) underwent comprehensive clinical interviews, psychosocial assessments, MINI diagnostic interview, and standardized self-report measures.ResultsMost participants were male (94%), and 80% met diagnostic criteria for gaming disorder. The average age of symptom onset was 16.0 years (SD = 4.6), with a mean duration of 5.5 years (SD = 4.6). Weekly gaming time averaged 50 hours (SD = 12.0, range 0–126). Although participants reported low levels of gaming disorder symptoms (measured by GDT) and psychological distress (measured by CORE-OM and RCADS), but 69% showed significant functional impairments based on clinician ratings using GAF and CGAS. ADHD symptoms were uniquely positively associated with both gaming disorder severity (β=0.39, p < 0.001) and psychological distress (β=0.34, p < 0.001). Psychological distress also increased with age (β=0.38, p=0.002).DiscussionAlthough many received a clinical diagnosis, the sample reported low levels of gaming disorder symptoms. They reported relatively low psychological distress but demonstrated substantial functional impairment. This may reflect gaming’s role as both an avoidance strategy and a way to meet psychological needs.ConclusionThese findings suggest that impaired everyday functioning is a defining clinical feature of this group. Treatment should not only address gaming behavior but also support patients in improving functioning across important areas of life, such as school, work, and relationships.